Transcriptional regulation of the CRK/DUF26 group of Receptor-like protein kinases by ozone and plant hormones in Arabidopsis - Wrzaczek, Michael (BioMed Central, 2010)
BACKGROUND: Plant Receptor-like/Pelle kinases (RLK) are a group of conserved signalling components that regulate developmental programs and responses to biotic and abiotic stresses. One of the largest RLK groups is formed by the Domain of Unknown Function 26 (DUF26) RLKs, also called Cysteine-rich Receptor-like Kinases (CRKs), which have been suggested to play important roles in the regulation of pathogen defence and programmed cell death. Despite the vast number of RLKs present in plants, however, only a few of them have been functionally characterized. RESULTS: We examined the transcriptional regulation of all Arabidopsis CRKs by ozone (O(3)), high light and pathogen/elicitor treatment - conditions known to induce the production of reactive oxygen species (ROS) in various subcellular compartments. Several CRKs were transcriptionally induced by exposure to O(3 )but not by light stress. O(3 )induces an extracellular oxidative burst, whilst light stress leads to ROS production in chloroplasts. Analysis of publicly available microarray data revealed that the transcriptional responses of the CRKs to O(3 )were very similar to responses to microbes or pathogen-associated molecular patterns (PAMPs). Several mutants altered in hormone biosynthesis or signalling showed changes in basal and O(3)-induced transcriptional responses. CONCLUSIONS: Combining expression analysis from multiple treatments with mutants altered in hormone biosynthesis or signalling suggest a model in which O(3 )and salicylic acid (SA) activate separate signaling pathways that exhibit negative crosstalk. Although O(3 )is classified as an abiotic stress to plants, transcriptional profiling of CRKs showed strong similarities between the O(3 )and biotic stress responses.